Gender mainstreaming : conceptual framework, methodology and presentation of good practice (Council of Europe Pub. StrasbourgFR, 1998)
Seeks to provide guidance for gender mainstreaming both in the public and private sectors. Explains what gender mainstreaming is and discusses how it relates to gender equality policy. Examines the pre-requisites for gender mainstreaming as well as the tools, techniques and personnel that will be involved in its implementation. Advises on the construction of a mainstream policy plan and provides examples of gender mainstreaming efforts.
Bibliography: p. 86-88. Located in the Learning Resource Centre